PENURUNAN INTENSITAS WARNA REMAZOL RED RB 133 DALAM LIMBAH BATIK DENGAN ELEKTROKOAGULASI MENGGUNAKAN NaCl - Fatimah, Nurul; -, Alimuddin; Gunawan, Rahmat (JURNAL ATOMIK, 2018)
A decrease in the intensity of dye Remazol Red RB 133 in batik waste with electrocoagulation method using electrodes aluminum and stainless steel has been done. Analysis was performed using a spectrophotometer Visibel. The results showed that the optimum effect of adding NaCl at a concentration 7 g/L with degradation was 84.95% percent, optimum contact time 60 minutes with degradation was 86.36%, stronger optimum voltage 12 Volts with degradation was 94.31% and pH optimum at pH 4 with degradation was 96.86%. Electrocoagulation in optimum condition dye Remazol Red RB 133 produces an average degradation was 96.41%, and electrocoagulation of batik waste obtained an average degradation was 91.38%.